Illuminating the hidden world of calcium ions in plants with a universe of indicators. Issue 2 (30th August 2021) - Grenzi, Matteo; Resentini, Francesca; Vanneste, Steffen; Zottini, Michela; Bassi, Andrea; Costa, Alex
Abstract : The tools available to carry out in vivo analysis of Ca 2+ dynamics in plants are powerful and mature technologies that still require the proper controls.